2013
DOI: 10.1186/1471-2474-14-275
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the quality of international orthopedic medical mission trips using the blue distinction criteria for knee and hip replacement centers

Abstract: BackgroundSeveral organizations seek to address the growing burden of arthritis in developing countries by providing total joint replacements (TJR) to patients with advanced arthritis who otherwise would not have access to these procedures. Because these mission trips operate in resource poor environments, some of the features typically associated with high quality care may be difficult to implement. In the U.S., many hospitals that perform TJRs use the Blue Cross/Shield’s Blue Distinction criteria as benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…One such catalyst for change was the Operation Walk Boston research program, which assesses the quality and outcomes of care provided by the mission 18,19 . The research was seen as a motivating force for change.…”
Section: Catalysts For Changementioning
confidence: 99%
See 1 more Smart Citation
“…One such catalyst for change was the Operation Walk Boston research program, which assesses the quality and outcomes of care provided by the mission 18,19 . The research was seen as a motivating force for change.…”
Section: Catalysts For Changementioning
confidence: 99%
“…This program has partnered with a local hospital (Hospital General de la Plaza de la Salud [Hospital HGPS]) to provide pro-bono total joint arthroplasty to economically disadvantaged patients. We have documented positive patient outcomes 18 and high-quality care 19 in association with the Operation Walk Boston program. The specific goals of this investigation were to determine (1) what changes have occurred at Hospital HGPS as a result of the knowledge and skills imparted by Operation Walk Boston and (2) whether the volunteer experience influenced how the participants provide care in the U.S.…”
mentioning
confidence: 97%
“…Using the Centers of Excellence criteria, a study found that Op-Walk Boston scored 71 points of a possible 100; a score of 60 qualifies as a Center of Excellence 21 . Op-Walk Boston was especially successful in satisfying process-based criteria, reflecting the capacity of the organization to collaborate with HGPS to implement high-quality processes of care, even in a resource-constrained environment.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, despite the cost and complexity of these surgeries, hip and knee replacement are among medicine’s most cost-effective surgeries. Sadly, these surgeries are unavailable in many communities around the world [ 6 , 7 ]. For example, over the last 5 years in Pernambuco, Brazil, rates of hip and knee replacement declined at a time of increasing need, resulting in several thousands of patients wait-listed for surgery [ 8 ].…”
Section: Introductionmentioning
confidence: 99%